Influence of hyperthermic intraperitoneal chemotherapy on renal blood perfusion - Liesenfeld, Lukas; Brandl, Andreas (Langenbeck's archives of surgery, 2023)
Hyperthermic intraperitoneal chemotherapy (HIPEC) is accompanied with an increased risk of acute kidney injury (AKI). Whether AKI is induced by chemotoxicity or hyperthermia-related changes in renal perfusion remains controversial. The influence of HIPEC on renal perfusion has not been evaluated in patients yet.
Gesehen am 05.07.2023